Differences in structural connectivity between diabetic and psychological erectile dysfunction revealed by network-based statistic: A diffusion tensor imaging study - Chen, Jianhuai; Wu, Jindan; Huang, Xinfei; Sun, Rui; Xiang, Ziliang; Xu, Yan; Chen, Shi; Xu, Weilong; Yang, Jie; Chen, Yun (Frontiers in Endocrinology, 2022)
Introduction: Type 2 diabetes mellitus (T2DM) has been found to be associated with abnormalities of the central and peripheral vascular nervous, which were considered to be involved in the development of cognitive impairments and erectile dysfunction (ED). In addition, altered brain function and structure were identified in patients with ED, especially psychological ED (pED). However, the similarities and differences of the central neural mechanisms underlying pED and T2DM with ED (DM-ED) remained unclear. Methods: Diffusion tensor imaging (DTI) data were acquired from 30 T2DM, 32 ED, 31 DM-ED patients and 47 healthy controls (HCs). Then the whole-brain structural networks were constructed, which were mapped by connectivity matrices (90×90) representing the white matter between 90 brain regions parcellated by the anatomical automatic labeling (AAL) template. Finally, the method of network-based statistic (NBS) was applied to assess group differences of the structural connectivity. Results: Our NBS analysis demonstrated 3 subnetworks with reduced structural connectivity in DM, pED and DM-ED patients when compared to HCs, which were predominantly located in the prefrontal and subcortical areas. Compared with DM patients, DM-ED patients had an impaired subnetwork with increased structural connectivity, which were primarily located in the parietal regions. Compared with pED patients, an altered subnetwork with increased structural connectivity was identified in DM-ED patients, which were mainly located in the prefrontal and cingulate areas. Conclusion: These findings highlighted that reduced structural connections in the prefrontal and subcortical areas were the similar mechanisms associated with pED and DM-ED. However, different connectivity patterns were found between pED and DM-ED and the increased connectivity in the frontal-parietal network might due to the compensation mechanisms that were devoted to improving erectile function.